PENGARUH PROGRAM KOKURIKULER KEWIRAUSAHAAN TERHADAP KREATIVITAS DAN MINAT BERWIRAUSAHA SISWA SMA NEGERI 2 PEKANBARU - Tahi Pardamean Sitorus; Gusnardi; Maharani (STKIP Subang, 2026)
This study aims to determine the influence of the entrepreneurship co-curricular program on the creativity and entrepreneurial interest of Grade X students at SMA Negeri 2 Pekanbaru. The study employs a quantitative approach with an associative research design. The population consists of 445 Grade X students at SMA Negeri 2 Pekanbaru who participated in the entrepreneurship co-curricular program (known as *Gelar Karya*). A sample of 82 students was determined using Slovin's formula and selected via proportional random sampling, ensuring that each class contributed a proportional number of students and had an equal chance of being selected as respondents. Data were collected using a Likert-scale questionnaire and analyzed through classical assumption tests and simple linear regression using SPSS software. The results indicate that the entrepreneurship co-curricular program has a positive and significant influence on student creativity, with a regression coefficient of 0.541 and a coefficient of determination (R-squared) of 0.517, representing a 51.7% contribution. The program also has a positive and significant influence on student entrepreneurial interest, with a regression coefficient of 0.410 and a coefficient of determination (R-squared) of 0.251, representing a 25.1% contribution. The findings reveal that the entrepreneurship co-curricular program exerts a greater influence on creativity than on entrepreneurial interest. Thus, a project-based entrepreneurship co-curricular program can serve as an effective learning strategy for developing students' creativity and entrepreneurial interest.